2011
DOI: 10.1590/s0037-86822011005000045
|View full text |Cite
|
Sign up to set email alerts
|

Late onset sepsis and intestinal bacterial colonization in very low birth weight infants receiving long-term parenteral nutrition

Abstract: Introduction:The purpose of this study was to establish the late onset sepsis (LOS) rate of our service, characterize the intestinal microbiota and evaluate a possible association between gut flora and sepsis in surgical infants who were receiving parenteral nutrition (PN). Methods: Surveillance cultures of the gut were taken at the start of PN and thereafter once a week. Specimens for blood culture were collected based on clinical criteria established by the medical staff. The central venous catheter (CVC) ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
2
10
0
7
Order By: Relevance
“…The VLBW infants using parenteral nutrition, who are strongly exposed to the NICU environment, to the colonization of the non-inserted distal catheter tip due to handling by the health team professionals and contact with the microbiota of their own skin, represent important risk factors, as mentioned in different studies that observed high rates of blood infections associated with central venous catheters. (4,8,13,(17)(18)(19) In this study, the arterial umbilical catheter was 8.5 times more associated with the occurrence of late sepsis, in line with other association studies between hospital infections and venous catheters. (17,19) The blood infections related to the use of venous catheter are reported to be the most common at the NICU, and mostly result from technical errors in the installation and care for the insertion site and in catheter handling.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The VLBW infants using parenteral nutrition, who are strongly exposed to the NICU environment, to the colonization of the non-inserted distal catheter tip due to handling by the health team professionals and contact with the microbiota of their own skin, represent important risk factors, as mentioned in different studies that observed high rates of blood infections associated with central venous catheters. (4,8,13,(17)(18)(19) In this study, the arterial umbilical catheter was 8.5 times more associated with the occurrence of late sepsis, in line with other association studies between hospital infections and venous catheters. (17,19) The blood infections related to the use of venous catheter are reported to be the most common at the NICU, and mostly result from technical errors in the installation and care for the insertion site and in catheter handling.…”
Section: Discussionsupporting
confidence: 90%
“…(4,8,13,(17)(18)(19) In this study, the arterial umbilical catheter was 8.5 times more associated with the occurrence of late sepsis, in line with other association studies between hospital infections and venous catheters. (17,19) The blood infections related to the use of venous catheter are reported to be the most common at the NICU, and mostly result from technical errors in the installation and care for the insertion site and in catheter handling. (20) The occurrence of late neonatal sepsis and its relation with the NICU environment and the invasive procedures the infants are submitted to have been widely discussed in studies undertaken in the large urban centers of Brazil and internationally.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations